The role of financial development in poverty reduction - Johan Rewilak (Review of Development Finance, 2017)
This paper investigates whether financial development is conducive in poverty reduction. Separating financial development into four categories and using newly available data this paper finds that both financial deepening and greater physical access is beneficial in reducing the proportion of people below the poverty line. Using alternative measures of financial instability, the results also challenge existing findings that it may increase the incidence of poverty. In addition, the results remain robust even when controlling for mobile money, providing a further valuable contribution to the literature.
Keywords: G21; I3; O16; 650; Financial development; Poverty reduction; Mobile money